2020
DOI: 10.3390/coatings10100963
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Characterization of Cu2MnSnS4 Thin Films Synthesized by Spray Pyrolysis under Air Atmosphere

Abstract: The direct synthesis of chalcopyrite Cu2MnSnS4 (CMTS) thin films by a spray pyrolysis technique on glass substrates under oxidative conditions (ambient atmosphere and using compressed air as a carrier gas instead of nitrogen) was studied. The effect of the deposition temperature on the structural, chemical composition, and optical and electrical properties of thin films has been assessed. X-ray diffraction study reveals that the tetragonal stannite structure crystallizes with a [112] preferential orientation f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 52 publications
(61 reference statements)
4
5
0
Order By: Relevance
“…This shift may arise from the micro-strain induced when the additives are incorporated during the film growth. The broadening of the diffraction peaks is an indication of the nano size of prepared material, which is in agreement with the previous reported results reported by Dridi et al [6].…”
Section: Results Of Xrdsupporting
confidence: 93%
See 1 more Smart Citation
“…This shift may arise from the micro-strain induced when the additives are incorporated during the film growth. The broadening of the diffraction peaks is an indication of the nano size of prepared material, which is in agreement with the previous reported results reported by Dridi et al [6].…”
Section: Results Of Xrdsupporting
confidence: 93%
“…The stress caused due to drying of thin films are primarily responsible for crack generation. During heating, the lowermost layer of the film bound to the substrate does not relieve the stress due to the subsequent coatings, which is in agreement with other reports [2,6].…”
Section: Fesem Analysissupporting
confidence: 92%
“…We can indicate from Table 4, the sheet resistance values decreased with dip-coating cycle increased, this behaviour is due more density and homogeneity of CNTS sample dip-coater at 6 cycles. The values of resistivity and sheet resistance are comparable to the other research groups [51,52]. The values of electrical conductivity of the films deposited using 4 and 5 cycles are lower, the electrical conductivity of the CNTS thin film deposited at 6 cycles is more adaptable for solar cell applications, probably the existence of secondary phase NiS improve the electrical characteristics of CNTS thin films.…”
Section: = ℎ × (11)supporting
confidence: 82%
“…The average crystal sizes of the FeNi@SiO 2 particles obtained at a T p of 300, 400, 500, 600, and 700 °C were 46.6, 46.7, 54.0, 54.4, and 57.9 nm, respectively. This increase in the crystal size with T p suggested that higher T p induces crystal growth of the FeNi alloy. , …”
Section: Resultsmentioning
confidence: 93%